2017
DOI: 10.3847/1538-4357/aa774a
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet-based Characterization of Small-scale Solar Emission Features at Low Radio Frequencies

Abstract: Low radio frequency solar observations using the Murchison Widefield Array have recently revealed the presence of numerous weakshort-livednarrowband emission features, even during moderately quiet solar conditions. These nonthermal features occur at rates of many thousands per hour in the 30.72 MHz observing bandwidth, and hencenecessarily require an automated approach for their detection and characterization. Here, we employ continuous wavelet transform using a mother Ricker wavelet for feature detection f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 33 publications
4
27
1
Order By: Relevance
“…(e.g. Mercier & Trottet 1997;Iwai et al 2014;Mugundhan et al 2016;Suresh et al 2017). A similar situation is likely to prevail here.…”
Section: Implications Of the Non-thermal Radio Emissionssupporting
confidence: 53%
“…(e.g. Mercier & Trottet 1997;Iwai et al 2014;Mugundhan et al 2016;Suresh et al 2017). A similar situation is likely to prevail here.…”
Section: Implications Of the Non-thermal Radio Emissionssupporting
confidence: 53%
“…A mixture of plasma emission and thermal emission may also help to explain why our higher-frequency Stokes V maps are not well-correlated with the LOS field structure. One of the MWA's main contributions thus far has been to demonstrate the prevalence of very weak nonthermal emissions (Suresh et al, 2017). Sharma, Oberoi, and Arjunwadkar (2018) report that up to 45 % of the total intensity outside of nominal burst periods may be nonthermal during moderately active periods, and preliminary imaging analyses suggest that nonthermal components are present to varying degrees in every environment.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed non-imaging investigations of weak impulsive nonthermal emissions have been carried out using the MWA Phase I with the aim of providing robust statistics on these emissions. Using an automated continuous wavelet transforms based approach, Suresh et al (2017) found that these impulsive emissions take place at the rate of many thousand per hour (as measured across 30.72 MHz bandwidth). Individual emission features were found to last for 1-2 s and span 4-5 MHz in bandwidth and ∼ 1 − 100 SFU 5 in peak flux densities.…”
Section: Weak Non-thermal Emissionmentioning
confidence: 99%